FORMULASI TABLET HISAP EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) YANG MENGANDUNG FLAVONOID DENGAN KOMBINASI BAHAN PENGISI MANITOL-SUKROSA - Yohanes Juliantoni; Mufrod Mufrod (Faculty of Pharmacy, Universitas Gadjah Mada, 2013)
Flavonoid compounds found on the leaves of the guava are known to have an antibacterial activity. The aim of this study is to formulate an acceptable guava leaf extract preparations. Extract of guava leaves was formulated into several dosages of lozenges in combination with fillers manitol-sucrose. A Simple method of Lattice Design was used to know the influence of the combination physical properties of granule and lozenges and also predicting which formula is optimal. The extract was made by maceration of simplisia using ethanol 70%, thickened and then dried using the tool freeze dryer. The lozenges was created in 5 formula based on a combination of sucrose: manitol, F1 (0%: 100%); F2 (25% 75%); F3 (50%: 50%); F4 (75%: 25%); F5: 25% (75%) using a 5% aqueous gelatin as a binder. The dried granule then mixed with a lubricant and tested for the properties such as free flowing. The resulting lozenges were tested of its uniformity of weight, hardness tested tablets, fragility and responses to the taste. Simple lattice equation design and optimum formula predicted using Design software Expert version 8.0.5.2. Changes in the proportion of sucrose-manitol combinations affect the physical properties of granule and lozenges. Based on an analysis using the Design software Expert version 8.0.5.2, the optimal formula is given by a combination of manitol-sucrose 82,28%: 17.72%.